Analisis Sentimen Komentar Mahasiswa Terhadap Dosen Mata Kuliah Pada Aplikasi SIMAT - syahroni, abd wahab (Jurnal PROCESSOR, 2023)
Assessment in the form of multiple choices is very easy to do, but not for assessment in the form of descriptions or sentences. In the SIMAT application at the University of Madura, there is a feature for student comments on course lecturers in the form of sentences. Students fill in comments at the end of each semester. Until now, the results of the assessment of student comments have never been given. Sentiment Analysis is one of the techniques in the field of Natural Language Processing (NLP) that studies attitudes, feelings, judgments and people's emotions about something. By using Sentiment Analysis on student comments, it can quickly provide results whether the accumulated student ratings are positive, negative or neutral. This research has succeeded in giving sentiment analysis values to student comments and displaying them in graphical and wordcloud form. From the trial data for 1 course with 21 students who filled in comments, the resulting sentiment analysis value was positive 12, neutral 9, and negative 0 with a value of accuracy, precision, recall and f1 score of 100%.